Surgical effect and prognostic factors of myasthenia gravis with thymomas - Tian, Wenxin (Thorac Cancer, 2020)
BACKGROUND: To evaluate the surgical effect and prognostic factors of extended thymectomy for myasthenia gravis (MG) patients with thymomas. METHODS: Patients with MG with thymomas who underwent extended thymectomy at Peking University People's Hospital and Beijing Hospital between January 2010 and December 2018 were retrospectively enrolled. Patients were followed up by telephone or outpatient record review . Statistical analyses were performed using SPSS version 19.0. RESULTS: A total of 194 patients were included in this study. According to the Osserman classification, there were 56 type I, 52 type IIa, 67 type IIb, 14 type III, and five type IV. Video‐assisted thoracoscopic surgery (VATS) thymectomies were performed in 137 patients, and transthymectomies in 57 patients. The average operation time was 136.6 ± 46.5 minutes, average blood loss was 129.3 ± 287.4 mL, and average postoperative stay was 8.3 ± 7.4 days. A total of 170 patients (87.6%) were successfully followed up. The median follow‐up period was 45 months, and the five‐year overall survival (OS) rate was 81.9%. Cox regression analysis demonstrated that age, Masaoka stage, and recurrence were prognostic factors of OS. Tumor recurrence tended to occur in patients with Masaoka stage III + IV, and age was a protective factor. A total of 20 patients experienced postoperative myasthenic crisis (POMC). Univariate analysis indicated that presence of bulbar symptoms, surgical procedure, and blood loss were risk factors for POMC, but multivariate analysis only indicated the presence of bulbar symptoms as an independent risk factor. A total of 162 patients were evaluated for post intervention MG status. A total of 55 patients achieved complete stable remission; the overall effective rate was 84.5%. Older patients and those with B‐type thymomas had a lower probability of achieving complete stable remission. Efficacy was similar in patients who underwent VATS or the transsternal procedure. CONCLUSIONS: Age, Masaoka stage, and recurrence were prognostic factors of OS. Presence of bulbar symptoms was an independent risk factor for POMC. Age and World Health Organization classification influence the postoperative effect of MG. KEY POINTS: Significant findings of the study Age, Masaoka stage, and recurrence were prognostic factors of OS for MG with thymomas. The presence of bulbar symptoms was an independent risk factor for POMC. Age and World Health Organization classification may influence the postoperative effect of MG. What this study adds Our study had a relatively large sample size of MG patients with thymomas only. We emphasize the analysis of the postoperative effect of MG and overall survival for these patients, which is a complement to previous studies.